Spermine-mediated metabolic homeostasis improves growth and stress tolerance in creeping bentgrass (Agrostis stolonifera) under water or high-temperature stress - Li, Zhou; Cheng, Bizhen; Wu, Xing; Zhang, Yan; Feng, Guangyan; Peng, Yan (Frontiers in Plant Science, 2022)
Plants have developed diverse defense strategies to reduce detrimental effects of a wide range of environmental stresses. Objectives of this study were to explore the function of spermine (Spm) on mediating growth and physiological changes in water homeostasis, photosynthetic performance, and oxidative damage, and further to examine regulatory mechanism of Spm on global metabolites reprogramming and associated metabolic pathways in horticultural creeping bentgrass (Agrostis stolonifera) under water stress and heat stress. The 21-days-old plants were pretreated with or without 100 μM Spm for 3 days and then subjected to water stress (17% polyethylene glycol 6000), high temperature stress (40/35°C, day/night), or normal condition (control without water stress and heat stress) for 18 days. Results demonstrated that exogenous application of Spm could significantly increase endogenous polyamine (PAs), putrescine (Put), spermidine (Spd), and Spm contents, followed by effective alleviation of growth retardant, water imbalance, photoinhibition, and oxidative damage induced by water stress and heat stress. Metabolites profiling showed that a total of 61 metabolites were differentially or commonly regulated by Spm in leaves. Spm upregulated the accumulation of mannose, maltose, galactose, and urea in relation to enhanced osmotic adjustment (OA), antioxidant capacity, and nitrogen metabolism for growth maintenance under water stress and heat stress. Under water stress, Spm mainly induced the accumulation of sugars (glucose-1-phosphate, sucrose-6-phosphate, fructose, kestose, maltotriose, and xylose), amino acids (glutamic acid, methionine, serine, and threonine), organic acids (pyruvic acid, aconitic acid, and ketoglutaric acid) involved in respiratory pathway, and myo-inositol associated with energy production, ROS-scavenging system, and signal transduction. In response to heat stress, the accumulation of alanine, glycine, gallic acid, malic acid, or nicotinic acid was specifically enhanced by Spm contributing to improvements in antioxidant potency and metabolic homeostasis. Current study provides novel evidence of Spm-induced tolerance to water stress and heat stress associated with global metabolites reprogramming in favor of growth maintenance and physiological responses in horticultural plants.